Branding Image Management As a Strategy To Enhance Competitiveness - Setyaningsih, Rini; Wati, Ira; Ghifari, Mahdini Al; Sari, Arrum Intan; kasheem, Majdy (Institut Agama Islam An-Nawawi Purworejo, 2024)
This research aims to analyze the comparison of branding image management in improving competitiveness between As-Shofa Islamic High School and Az-Zuhra Islamic School Pekanbaru. This research uses a qualitative approach with data collection techniques that include observation, interviews, and documentation. Data were analyzed through data collection, data reduction, data presentation, verification, conclusion drawing, and data triangulation techniques. The results of this study First, As-Shofa Islamic High School applies branding image management through the stages of Planning, Organizing, Actuating, and Controlling, with a focus on creating uniqueness, excellence, and strength. This school has two excellent programs, namely academic programs and student programs. These programs are more dominantly oriented towards higher education and general goals.Second, Az-Zuhra Islamic High School Pekanbaru also applies image branding management with the stages of Planning, Organizing, Actuating, and Controlling, with an emphasis on excellence, uniqueness, and strength. The flagship programs at this school include Tahsin and Tahfidz, Worship, and Character Building, which are dominantly oriented towards developing students' religious character. This research shows significant differences in image branding strategies between SMA Islam As-Shofa and SMA Az-Zuhra Islamic School Pekanbaru. As-Shofa Islamic High School focuses more on academic and general programs for higher education, while Az-Zuhra Islamic High School emphasizes more on religious character development. This finding provides insight into how differences in branding image strategies can affect the competitiveness of Islamic educational institutions.